2016
DOI: 10.5897/ajar2016.11444
|View full text |Cite
|
Sign up to set email alerts
|

Seeding density of Brachiaria ruziziensis intercropped with grain sorghum and effects on soybean in succession

Abstract: Sorghum is an alternative crop to produce grains in the off-season in Brazilian Cerrado and the intercropping with Brachiaria species enable to produce dry matter on the soil surface for a longer time. However, there is limited information on Brachiaria ruziziensis seed density to be applied to intercropping with sorghum without causing decreases in sorghum grain yield. The objective of the study was to evaluate the seeding density of B. ruziziensis in different intercropped systems with grain sorghum grown af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Due to the differences in the study regions and genetics, in addition to the time of implementation of the system, grain yields in the present study were lower than reported by [44], higher than reported by [26,36] and [45] similar to those reported by [26] for intercropping of grain sorghum with Brachiaria species in the second crop season for grain and biomass production.…”
Section: Sorghum Cropcontrasting
confidence: 69%
“…Due to the differences in the study regions and genetics, in addition to the time of implementation of the system, grain yields in the present study were lower than reported by [44], higher than reported by [26,36] and [45] similar to those reported by [26] for intercropping of grain sorghum with Brachiaria species in the second crop season for grain and biomass production.…”
Section: Sorghum Cropcontrasting
confidence: 69%
“…Therefore, intercropping with Brachiaria sorghum provided no limitation on the soybean crops in succession. In other research papers, increases were recorded in yields when the culture was planted in succession with the intercropping system (Borges et al, 2016;Moraes et al, 2014). The benefits of the integration of grasses have been observed in the soil structure with the use of plants such as sorghum and Brachiaria, which have deep root systems and are bulky and aggressive (Kluthcouski et al, 2004).…”
Section: Soybean Cropmentioning
confidence: 93%
“…Moreover, this type of intercropping could generate other benefits, such as straw formation for the no‐tillage system (Andrade et al., 2020; Borges et al., 2016), weed suppression (Buffara et al., 2018; Timossi et al., 2018), soil protection and maintenance of its moisture (Buffara et al., 2018), besides soil carbon sequestration and greenhouse gases mitigation (Amadori et al., 2022; Bratti et al., 2022).…”
Section: Introductionmentioning
confidence: 99%